Screening of local herbs against Asperfillus flavus - Nur Amalina, Omar (Universiti Malaysia Sarawak, (UNIMAS), 2017)
Medicinally important plants have tremendous antimicrobial and antifungal potential, thus in this study, three local herbs commonly used in Malaysia were chosen to screen their antifungal activity. The rhizome of Alpinia galanga, and the leaves part of Cosmos caudatus, and Centella asiatica were tested against Aspergillus flavus using disc-diffusion and well-diffusion method. The herbs were oven-dried and ground into dry (powder) form before extracted using 80% methanol. It was concentrated by using rotary evaporator and undergo serial dilution to obtain several different concentrations (80, 90 and 100% concentration). On the 7th incubation day, the inhibition zones were obtained only from extracts of C. asiatica when tested using the well-diffusion method with 100% concentration has the highest inhibition zone diameter. The rest of the plant extracts exhibited minimal to none antifungal activities in both disc-diffusion and well-diffusion method.